Adult Buried Penis Repair with Escutcheonectomy and Split-Thickness Skin Grafting. Issue 8 (27th June 2018) - Strother, Marshall C.; Skokan, Alexander J.; Sterling, Matthew E.; Butler, Paris D.; Kovell, R. Caleb
Abstract: Aim: To describe a technique for surgical correction of adult buried penis, including a technique for skin graft harvesting from the escutcheonectomy specimen itself, with an emphasis on remaining open questions in the literature. Methods: We present our method for surgical correction of adult buried penis with a review of the literature. Main Outcome Measure: Components of successful buried penis repair include return of directed voiding, elimination of local skin inflammation and infection, improvement in hygiene, return of sexual functioning, cosmesis, and patient satisfaction. To date, there are no broadly accepted tools for comprehensive measurement of outcomes after buried penis repair. Results: Adult buried penis repair is generally associated with excellent rates of satisfaction and improvement in functioning. Currently available data are extremely limited; however, they do suggest that, when in doubt, more aggressive debridement of diseased tissue combined with split-thickness skin grafting may provide superior outcomes. Split-thickness skin grafts are associated with excellent rates of successful graft take, even in cases of severe preoperative pathology and patient comorbidity. Although these grafts come at the cost of some increased surgical morbidity, they are associated with low rates of major complications. Morbidity can be further significantly decreased by harvesting the graft from the excised escutcheon itself, a technique that we present here. Conclusion: Surgical correction of adult buried penis is safe and effective; however, future work is required to further optimize outcomes and reduce surgical morbidity.